Child offenders in Iran: legal analysis on the age of criminal responsibility and sentencing(in English) - Shohreh Mousavi; Rohimi Shapiee; Rohaida Nordin (Institut Kajian Rantau Asia Barat, 2012)
The age of criminal responsibility of children is important because of its relevance to children life. The minimum age of criminal responsibility of children is the lowest statutory age at which children may potentially be held criminally liable for infringements of the penal law in a given country. Thus, the area of children's rights includes the issue on age of criminal responsibility of children in international instruments as international standard. This article analyses the age of criminal responsibility of children in Iranian laws as a Member State of international instruments such as the United Nations Convention on the Rights of the Child (UNCRC) as the basic sources for the children‟s rights in international law. This article analyses the legal framework for the age of criminal responsibility of children under the Iranian laws especially the Islamic Penalties Act. This article also discusses the conduct of prosecution and sentencing of children in Iran. The methodology involves gathering relevant data from the specified documents and compiling databases in order to analyse the material and arrive at a more complete understanding on the issue. The results of this analysis can be used to determine the proper age of criminal responsibility of children in Iran, specifically, and to promote protection of the rights of child offenders in Iran, generally.